The Study on Farmers’ Knowledge and Behavior in Using of Chemicals for Protection and Pest Elimination in Pho Thale Sub-district, Pho Thale District, Phichit Province - Yeamkong, suphawadee; Ngoc, Tuan Nguyen; Kotom, Patthanun; Jaipong, Prapasiri; Noinumsai, Piyawadee; Yaemkong, Sirikranda; Seema, Pattapaporn (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2018)
The objective of this research was to study farmers’ knowledge and behavior in using of chemicals for protection and elimination on pest. The samples of the study were 322 farmers in Pho Thale Sub-district, Pho Thale District, Phichit Province. The samples were selected by purposive sampling. The data were collected by using of questionnaires (Cronbach’s alpha = 0.80) and analyzed with percentage, arithmetic mean, minimum, maximum and standard deviation. The results showed that most farmers were males (53.43%), the farmers’ average age was 54.56 ± 11.40 years old, and had primary school education level (77.56%). Most of the farmers cultivated rice (86.60%). Mainly source of investment funds for producing agriculture was from Bank for Agriculture and Agricultural Cooperatives (83.11%) and source of knowledge in using pesticides was from themselves (31.28%). Overall average mean scores of knowledge of farmers were medium (76.61%). Most farmers had the highest score of knowledge before using pesticides. The overall mean score of behavior in using pesticides was 3.85 ± 0.62 (high level). And most farmers had the highest score of behavior before using pesticides. Therefore, every organization should support and train them to use the pesticides appropriately.